Search for a new Z' gauge boson via the 𝑝⁢𝑝 → 𝑊±(*) → 𝑍′⁢𝜇±⁢𝜈 → 𝜇±⁢𝜇∓⁢𝜇±⁢𝜈 process in pp collisions at √s= 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physical review, 2024)
A search for a new 𝑍′ gauge boson predicted by 𝐿𝜇 −𝐿𝜏 models, based on charged-current Drell-Yan production, 𝑝⁢𝑝 →𝑊±(*) →𝑍′⁢𝜇±⁢𝜈 →𝜇±⁢𝜇∓⁢𝜇±⁢𝜈, is presented. The data sample used corresponds to an integrated luminosity of 140 fb−1 of proton-proton collisions at √𝑠 =13 TeV recorded by the ATLAS detector at the Large Hadron Collider. The search examines a final state of 3⁢𝜇 plus large missing transverse momentum. Upper limits are set on the 𝑍′ production cross section times branching ratio in the mass range of 5-81 GeV. After combining with the previous 𝑍′ search using the neutral-current Drell-Yan production with a 4⁢𝜇 final state, the most stringent exclusion limits to date are achieved in the parameter space of the 𝑍′ coupling strength and mass.
ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser und weitere 2867
Im Titel sind die Zeichen "±", "∓" und "(*)" hochgestellt
Gesehen am 14.10.2025